Research on Competency Optimization Path of Physical Education Teachers in Primary and Secondary Schools under the Background of "Double Reduction" Policy - Li, Qingmei (Journal of Educational Research and Policies, 2024)
The competence of physical education teachers in primary and secondary schools is a comprehensive evaluation standard to measure whether physical education teachers in primary and secondary schools can complete their work efficiently and produce excellent performance. Under the background of the "double reduction" policy, physical education in primary and secondary schools puts forward new requirements on teachers' competency from the aspects of education service consciousness, work initiative, teacher continuing education, psychological state adjustment, etc. In order to cope with the changes brought about by the implementation of the "double reduction" policy, this study proposes a six-dimensional optimization path for physical education teachers in primary and secondary schools, including: Strengthening the professional knowledge training of physical education teachers in primary and secondary schools; Pay attention to the training of PE teachers' professional skills; Promoting the improvement of the teaching ability of PE teachers in primary and secondary schools; Strengthen the basic professional quality training of PE teachers in primary and secondary schools; Strengthen the construction of social adaptability of PE teachers in primary and secondary schools; Improving the sustainable innovation ability of PE teachers in primary and secondary schools. In order to provide reference for the personal development and better work of primary and secondary school physical education teachers.